Constituents of flowers of Paeoniaceae plants, Paeonia suffruticosa and Paeonia lactiflora. (June 2015) - Ogawa, Keiko; Nakamura, Seikou; Sugimoto, Sachiko; Tsukioka, Junko; Hinomaru, Fusako; Nakashima, Souichi; Matsumoto, Takahiro; Ohta, Tomoe; Fujimoto, Katsuyoshi; Yoshikawa, Masayuki; Matsuda, Hisashi
Graphical abstract: Highlights: A new monoterpene glycoside, floralalbiflorin I, was isolated from the flowers of Paeonia suffruticosa . A new flavonol glycoside, lactifloraoside I, was isolated from the flowers of Paeonia lactiflora . Their chemical structures of the new constituents were elucidated. The major constituents significantly showed the inhibitory effects on Cu 2+ -induced LDL oxidation. 1, 2, 3, 4, 6-Penta- O -galloyl- β -d -glucopyranoside showed the most potent inhibitory effect. Abstract: A new monoterpene glycoside, floralalbiflorin I (1), and a new flavonol glycoside, lactifloraoside I (2), were isolated from the flowers of Paeonia suffruticosa and Paeonia lactiflora (Paeoniaceae) together with 28 known compounds. The chemical structures of the isolated compounds were elucidated on the basis of chemical and physicochemical evidence. Among the major constituents of P. suffruticosa and P. lactiflora flowers, 1, 2, 3, 4, 6-penta- O -galloyl- β -d -glucopyranoside (10) [inhibition: 42.4% at 1 μM] and flavonoids having the catechol moiety showed significant inhibitory effect on Cu 2+ -induced low-density lipoprotein (LDL) oxidation.